PERKEMBANGAN MANUSIA DALAM TINJAUAN PSIKOLOGI DAN AL-QUR'AN - Hanafi, Imam (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
Human development is basically a fixed pattern that must be experienced by every individual in general, besides that development is a process that involves growth from the stage of manufacture to continuing throughout a person's vulnerable life. In the Qur'an there are several ayat that show about human development. Therefore the developments contained in the Qur'an will be tried to be compared with the discipline of psychology, where by doing this study will provide new insights about the concept of human development hangs produced by western scientists actually already implied in the ayat of the Qur'an.